Effects of a single bout of high-intensity-interval exercise on cardiovascular autonomic, cerebrovascular, and cognitive function in people with spinal cord injury: A study protocol - Wenjie Ji; Jill M. Wecht; Hang Jin Jo; Filip Stefanovic; Jeffrey Miecznikowski; Nancy D. Chiaravalloti; Sue Ann Sisto (PLoS ONE, 2025)
Background Spinal cord injury (SCI) frequently disrupts the autonomic nervous system (ANS), impairing cardiovascular function and affecting cerebrovascular and cognitive functions. While high-intensity interval exercise (HIIE) is known to improve cardiovascular and cognitive functions in non-injured populations, its impact on these functions in individuals with SCI, especially those with high-level injuries, is not well-documented. Objective The primary aim of this study is to investigate the acute effects of a single bout of HIIE on ANS related-cardiovascular (ANS-CV) function in individuals with chronic SCI at or above T6. The secondary aims are to examine the acute effects of the same HIIE bout on cerebrovascular dynamics and cognitive performance in this population. Methods In this prospective case-control study, 15 individuals with SCI at T6 or above and 15 age- and sex-matched uninjured controls will be assessed. Measures include heart rate, heart rate variability, blood pressure, systolic blood pressure variability, cerebral blood flow velocities, and cognitive performance, analyzed pre- and post-HIIE. The sit-up test and face-cooling test will be used to activate the ANS-CV system. Post-exercise assessments will begin 5 minutes after completing the HIIE session. Cardiovascular testing will be conducted first and is expected to last 36 minutes. Cerebrovascular and cognitive testing will follow, starting approximately 41 minutes after the HIIE session. Covariates such as physical activity levels, pre-morbid intelligence, and psychological distress will be considered. This study has been approved by the University at Buffalo Institutional Review Board (IRB) (Approval Number: MOD00013354) and registered on ClinicalTrials.gov (Registration Number: NCT06274658). Results We hypothesize that HIIE will improve cardiovascular and cerebrovascular functions and enhance cognitive performance in the SCI group. Data will be analyzed using linear mixed-effects models to evaluate the interaction effects of group and exercise. Conclusions This study is expected to fill the knowledge gap regarding the impact of HIIE on cardiovascular, cerebrovascular and cognitive functions in individuals with SCI at or above T6. The findings will provide crucial insights into immediate physiological responses while establishing foundational evidence for developing targeted, long-term exercise interventions to improve health outcomes in this population.